IR Spectra of Entrance and Exit Channels of Methane Molecule and Oxygen Atom Reaction at MP2 Theory - Sulaiman, Media Ismael (Iraqi Journal of Science, 2023)
IR spectra of entrance and exit channels of methane and radical oxygen reaction are predicted in the ground state energy. Ab initio calculations at perturbation theory (MP2) with Dunning correction- consistent basis set (aug-cc-pVDZ) have been used. The calculations predicted structures, vibrational frequencies and potential energy surface. Three van der Waals minima from three adiabatic potential energy surfaces have been predicted in entrance and exit channels. Vibration frequency of 3209 cm-1 and 3212 cm-1 of C-H stretching in entrance structures are predicted while O-H vibrational frequency is predicted to be at 3673 cm-1 in the other channel. The lowest energy structure in entrance channel has - 0.18 kJ/ mol minimum energy.